Indicators of the cell line of immunity in patients with generalized parodontitis and psychoemotional stress - Кононова, О. В. (Actual Dentistry, 2019)
Abstract. In the development of periodontal disease is important the presence of psychological stress in patients. This should be considered in the complex treatment of patients with periodontal disease. Objective. Determination of the parameters of the cell line system of immunity in patients with generalized periodontitis in conditions of psychoemotional stress. Material and research methods. This study was conducted on a group of 40 young patients. They were divided into the following 4 subgroups of 10 people each. First: clinically healthy individuals with no manifestations of stress with clinically ealthy periodontal tissues. The second: patients with generalized periodontitis without manifestations of stress. Third: persons with manifestations of psychological stress without visible lesions of periodontal tissues. Fourth: patients with generalized periodontitis ith manifestations of psychological stress. The level of psychological stress was assessed using questionnaires. All patients with generalized periodontitis were subjected to a thorough clinical examination of the oral cavity. Immunophenotyping of lymphocytes was performed in venous blood of patients by USA). Results. Determination of the parameters of subpopulation composition of lymphocytes: CD3+, CD4+, CD8+ in this category of patients showed a decrease in their absolute number in patients with periodontal disease (generalized periodontitis – 2nd subgroup), psychoemotional stress (3-rd subgroup) and in the case of a combination of periodontal disease and psychoemotional stress (4-th subgroup). Most of these changes are expressed in patients of the 4th ubgroup in the case of a combination of periodontal disease and psychoemotional stress. Conclusions. The conducted research allows to confirm a certain relationship between the manifestations of psychoemotional stress, periodontal disease (generalized periodontitis) and cellular immunity. Such a condition requires appropriate medical treatment of this group of patients with generalized periodontitis with manifestations of psychoemotional stress. Key words: generalized periodontitis, psychoemotional stress, cellular immunity.